2019
DOI: 10.1177/1971400919876621
|View full text |Cite
|
Sign up to set email alerts
|

Advanced magnetic resonance imaging of cortical laminar necrosis in patients with stroke

Abstract: Purpose The aim of this study was to assess the novel advanced magnetic resonance imaging findings of acute stage cortical laminar necrosis developing after complicated cardiovascular or abdominal surgery. Materials and methods This institutional review board-approved study included patients with postoperative stroke due to cortical laminar necrosis imaged with magnetic resonance in the acute stage. Brain magnetic resonance imaging examinations were obtained on a 3T magnetic resonance scanner within 48 hours o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This typically occurs following a hypoxic-ischemic event, in which the ischemia is not severe enough to affect less metabolically active white. [ 1 ] Cortical ischemia demonstrates diffusion restriction within several hours after an initial insult; this diffusion restriction fades over several weeks. T1 shortening may appear 2 weeks after the precipitating event.…”
Section: Discussionmentioning
confidence: 99%
“…This typically occurs following a hypoxic-ischemic event, in which the ischemia is not severe enough to affect less metabolically active white. [ 1 ] Cortical ischemia demonstrates diffusion restriction within several hours after an initial insult; this diffusion restriction fades over several weeks. T1 shortening may appear 2 weeks after the precipitating event.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical laminar necrosis (CLN) refers to ischemic injury of selective neuronal cortical layers due to hypoxic injury [1 , 2] . Usually, it occurs secondary to infarcts or hypoxia, however other causes, including hypoglycemia, status epilepticus, and immunosuppressive therapy have been described [3] . In the chronic phase, CLN is characterized by T1-hyperintensity following the gyri of the cerebral cortex without the involvement of the underlying white matter (WM) and atrophy of the cortical structures on T1-weighted MRI images [4] .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Finding these phase changes Acute symptoms are particularly challenging as they usually appear two weeks after ischemia, peak in intensity around a month and then slowly disappear over 3 months to 2 years, and cortical atrophy may appear in the chronic phase. 1,7,8,9,10 Some studies have shown that T1 hypersignal reflects the presence of substances such as hemoglobin, lipid-laden macrophages, melanin, paramagnetic substances or protein-rich fluid, therefore, not being sec. undone to hemorrhagic transformation of cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Only a few case reports have evaluated diffusion-weighted imaging (DWI) abnormalities in the acute phase of CLN. 10 Thus, this entity still has several unexplored characteristics, with a significant gap in knowledge regarding the acute phase of CLN.…”
Section: Introductionmentioning
confidence: 99%